2008
DOI: 10.1080/14038190701433191
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy under discussion: A discourse analytic study of physiotherapy students’ clinical education

Abstract: Clinical education is asserted to be an important period in professional education, being an environment where deep conceptual understanding can develop. The aim of this study was to analyse the interaction between clinical educators and students during supervision discussion sessions in physiotherapy student's clinical education. The focus was on examining the meanings related to physiotherapy practice and the construction of these meanings by means of discussion. By analysing 10 videotaped supervision discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…However, in general, participants’ descriptions indicated a lack of EBP role models and an EBP culture. This is consistent with a previous study, which found only elements of EBP when analyzing the interaction between clinical educators and physiotherapy students during supervision discussion sessions ([66], p. 3–4). The main focus of supervisory interaction tended to be practical skill [67].…”
Section: Discussionsupporting
confidence: 93%
“…However, in general, participants’ descriptions indicated a lack of EBP role models and an EBP culture. This is consistent with a previous study, which found only elements of EBP when analyzing the interaction between clinical educators and physiotherapy students during supervision discussion sessions ([66], p. 3–4). The main focus of supervisory interaction tended to be practical skill [67].…”
Section: Discussionsupporting
confidence: 93%
“…Clinical education is widely considered to be the cornerstone of health care professionals’ education and is described as the key component that prepares health professionals for practical experiences (Kilminster et al 2007 ; Laitinen-Väänänen 2008 ). In the clinical environment, clinical education remains a powerful teaching context as it provides an authentic experience during which students are actively engaged in the learning process (Griffiths & Ursick 2004 ; Ker, Cantellon & Ambrose 2008 ; Webb 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…The categories in the coding frames were used as guiding instruments when interpreting and coding the data and when answers to the study questions were determined. The frames and categories, with their basis in three background theories, seemed to function sufficientl (57,58). All of the authors participated in the analysis to add to the power and credibility of the data interpretation.…”
Section: Discussionmentioning
confidence: 99%